PELAKSANAAN PENDAFTARAN PENEGASAN HAK MILIK ADAT BERDASARKAN PASAL 96 PERATURAN PEMERINTAH NOMOR 18 TAHUN 2021 TENTANG HAK PENGELOLAAN, HAK ATAS TANAH, SATUAN RUMAH SUSUN, DAN PENDAFTARAN TANAH (Studi di Kecamatan Sungai Kunyit, Kabupaten Mempawah) - RIYAN ADI PUTRA NIM. A1011191200 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstracProblems with the law in the land sector from the past until now have often occurred without synchronization and harmonization of laws governing land rights because land law has a very broad dimension, one of which is the new policy in Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flats Units, and Land Registration governing land, one of which regulates customary ownership of land, as stipulated in Part Two of Article II of UUPA Conversion Number 5 of 1960 which when converted to Property Rights. This thesis is entitled